Can Business Road Travel Be Safe? Experience of an International Organization - Goldoni Laestadius, J.; Selod, A. G.; Ye, J.; Dimberg, L.; Bliss, A. G. (2012)
BACKGROUND: Globally, more than 1.2 million people die on the roads every year, and unfortunately so do one or two operational travelers for the World Bank Group (WBG). METHODS: To investigate potentially preventable factors and improve the institution's road safety policies and practices, an electronic survey was designed in 2008 targeting about 16,000 WBG staff worldwide to inquire about road crashes and near crashes over the 3-year period. Also, questions were asked pertaining to contributing circumstances. Staff was encouraged to provide comments on prevention. A combined index based on the number of reported crashes and near crashes divided by person-days spent on mission in each country was used to rank the countries. RESULTS: A total of 3,760 responses were collected. There were 341 road crashes reported, about 1 in 175 missions. Seventy percent took place in taxis, and 40% of crash victims reported that seatbelts were not used. Contributing factors included driver's decision error, speeding, or road/weather conditions. On the basis of a combined index, a list of 36 high-risk countries is presented. A high correlation between crashes and near crashes (r = 0.89) justifies the method. CONCLUSIONS: Improved corporate policies will need to be developed to address preventable risk factors identified in the study.